The potential of using exosomes in modern medicine - Kosecka, Katarzyna; Rudziński, Patryk; Cieślik, Aleksandra; Jargieło, Anna; Kosieradzka, Karolina; Adamowicz, Dominik; Stańczyk, Justyna; Łopuszyńska, Inga; Wosińska, Alicja; Meliksetian, Astrik (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the work: The purpose of this article is to determine the potential for the application of exosomes in modern medicine, inferring from research directions in world literature. Among other things, this paper considers some of the most recent work in the fields of aesthetic medicine, dermatology and transplantation. Methodology and materials: The search was conducted using PubMed, Google Scholarship, Scopus and Web of Science databases. The search strategy was based on the following terms: exosomes, regenerative medicine, dermatology. The variety of available scientific works on exosomes raises the question in which of the fields of medicine they will be used the fastest and/or most commonly. Given that a significant part of research focuses on their use in skin treatments, it can be expected that it will be dermatology and/or aesthetic medicine, given its exceptional openness to the implementation of new techniques and the constant search for new solutions that allow physiologically or optically to oppose aging. In addition, the use of exosomes is characterized by a relatively low risk of life-threatening complications or permanent damage to health. However, the potential applications of exosomes in other fields of medicine should not be underestimated. Therefore, it can be expected that procedures and therapies using exosomes will also be developed and implemented independently in transplantology, cardiology, or other fields that can use exosomes as drug carriers or markers for early detection of complications or diseases.